2014
DOI: 10.1016/j.crad.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Static end-expiratory and dynamic forced expiratory tracheal collapse in COPD

Abstract: AIM: To determine the range of tracheal collapse at end-expiration among chronic obstructive pulmonary disease (COPD) patients and to compare the extent of tracheal collapse between static end-expiratory and dynamic forced-expiratory multidetector-row computed tomography (MDCT). MATERIALS AND METHODS: After institutional review board approval and obtaining informed consent, 67 patients meeting the National Heart, Lung, and Blood Institute (NHLBI)/World Health Organization (WHO) Global Initiative for Chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Another remark is the static nature of our set-up. O'Donnell et al concluded that the magnitude of static end-expiratory tracheal collapse does not predict excessive dynamic expiratory tracheal collapse in COPD patients [33]. Further research should elucidate whether dynamic measurements would support our results.…”
Section: Discussionmentioning
confidence: 46%
“…Another remark is the static nature of our set-up. O'Donnell et al concluded that the magnitude of static end-expiratory tracheal collapse does not predict excessive dynamic expiratory tracheal collapse in COPD patients [33]. Further research should elucidate whether dynamic measurements would support our results.…”
Section: Discussionmentioning
confidence: 46%
“…3739 However, we used a stringent 50% cutoff for CSA reduction despite scan acquisition with tidal exhalation, and thus detected the more severe cases. Recent studies have shown that with dynamic scans, even normal volunteers can have significant airway collapse, 38,39 and our measurements at tidal exhalation might be clinically more meaningful. Second, COPDGene includes smokers with an oversampling of participants with COPD.…”
Section: Discussionmentioning
confidence: 67%
“…To date, there have been few veterinary reports about changes in bronchial diameter related to respiratory phase, and bronchial diameters have only been measured at end inspiration or end expiration . In addition, there is no published report on the measurement of bronchial collapsibility during forced expiration in dogs, although bronchial collapsibility during dynamic expiration and end expiration have been actively studied in humans . This lack of related studies could cause misinterpretation of normal variation in the lower airways throughout respiration and the subsequent inaccurate diagnosis of bronchomalacia especially in dogs not undergoing bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%